Political Resistance in Qur’anic Legal Exegesis: Al-Jaṣṣās’s Opposition to The Umayyads in Aḥkām al-Qur’ān - Abdullah Khidhir (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2024)
This paper examines political tendencies in the interpretation of the Qur’an during the early medieval Islamic period. It investigates the Aḥkām al-Qur’ān, an exegetical text based on jurisprudential genre, written by al-Jaṣṣās (305-370 AH) and elaborates on his critical stance towards the Umayyad leadership. A socio-political analysis is used to trace the author’s political situation, ideology, and school of thought, which illuminates his tendencies. This study shows that even though Aḥkām al-Qur’ān has a jurisprudential basis, it also conveys a political message intended to oppose the Umayyads. Several verses (9:29, 1:1, 22:41, 24:45 and 49:9) were introduced to demonstrate his critical standpoint against the Umayyads, who were portrayed as an imperfect government. This finding, therefore, supports the claim that schools of fiqh are not always independent, but often align with particular political tendencies. I argue that the Hanafi school invested considerably in al-Jaṣṣās, not only in terms of his jurisprudential reasoning (ijtihād), but also in his critical and hostile attitude towards the Umayyad leaders.